2021
DOI: 10.3390/ma14216317
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Pure SiC Ceramics by HTPVT Induced by Seeding with SiC Nanoarrays

Abstract: Dense SiC ceramics were fabricated by high-temperature physical vapor transport (HTPVT) growth process using SiC nanoarrays as the crystal seeds, which was obtained by vacuum heat treatment of amorphous SiC films prepared by plasma-enhanced chemical vapor deposition (PECVD) with a porous anodic aluminum oxide (AAO) template. In the HTPVT process, two-step holding was adopted, and the temperature at the first step was controlled at 2100 and 2150 °C to avoid SiC nanoarrays evaporation, and the grain size of SiC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Masuda et al, in 1995 [74], proposed the two-step anodization method for AAO technology, as shown in Figure 7, which laid the foundation for the AAO processes and applications. Many groups still follow this approach [128][129][130][131] today for AAO-related research. The first AAO can leave a pre-pattern after the removal process, making the hexagonal structure more regular during the second step of anodization.…”
Section: Conventional Two-step Processmentioning
confidence: 99%
“…Masuda et al, in 1995 [74], proposed the two-step anodization method for AAO technology, as shown in Figure 7, which laid the foundation for the AAO processes and applications. Many groups still follow this approach [128][129][130][131] today for AAO-related research. The first AAO can leave a pre-pattern after the removal process, making the hexagonal structure more regular during the second step of anodization.…”
Section: Conventional Two-step Processmentioning
confidence: 99%